I'm reading a book Lie groups, Lie algebras, cohomology and some applications in physics by Azcarraga and Izquierdo, and on page 347, when deriving the exact form of the central extension term I came to a bit which I don't understand how they got it.

The algebra is given by


And using the Jacobi identity I get


If we transform the generators of the algebra, by adding a constant $b(m)$, the algebra itself won't change: $L_m\to L_m'=L_m+b(m)$. After putting that in the first expression I get


where $c_{m,n}'=c_{m,n}+c_{m,n}^{\textrm{cob}}$, and $c_{m,n}^{\textrm{cob}}=-b(m+n)(m-n)$ is the coboundary generated by $b(m)$.

Now starts the part that I don't know where they got it from. They say that taking this into the account we see that, with

$$b(m)=\frac{1}{m}c_{m,0},\quad m\neq 0$$ $$b(0)=\frac{1}{2}c_{1,-1}$$

we have

$$c_{0,n}'=c_{0,n}+\frac{1}{n}c_{n,0}\ n=0,\quad n\neq 0$$ $$c_{1,-1}'=c_{1,-1}-\frac{1}{2}c_{1,-1}2=0$$

I get why the last one is 0 (the factors cancel each other out), but why is the $c_{0,n}'=0$? And from where do they get the relations with $b(m)$ and $b(0)$?

Also, how does that come to play when they set $p=0$ in the equation for $c$ in the Jacobi identity, and getting the result


I have the feeling like there are some steps that were ommited. I cannot reproduce this last equation from Jacobi identity one.

Any help will be appreciated.

  • $\begingroup$ Perhaps math.stackexchange might be better suited for this problem? $\endgroup$
    – Kyle Kanos
    Oct 13 '13 at 2:01
  • $\begingroup$ I posted it here because it's usually used in physical context. But if a mod can migrate it there than that'd be great :) $\endgroup$
    – dingo_d
    Oct 13 '13 at 11:24

Let us consider the most general central-charge extension of the Witt algebra, given by \begin{equation} \begin{split} \left[ L_m, L_n \right] = \left( m - n \right) L_{m+n} + c(m, n) \end{split} \end{equation} Clearly, we must have $c(m,n) = -c(n,m)$. Naively, central extensions are parameterized by a function $c(m,n)$. However, we now show that by appropriately redefining the generators $L_m$, we can rewrite any general central charge extension into the standard form where the function $c(m,n)$ is parameterized by a single $c$-number. First note that the algebra takes the same form if we redefine $L_m \to L_m + a(m)$ where $a(m)$ is a $c$-number function. Under this redefinition, the function $c(m,n)$ changes to \begin{equation} \begin{split} c(m, n) \to c(m,n) + \left( m - n \right) a(m + n) \end{split} \end{equation} By choosing $a(m) = - \frac{1}{m} c(m,0)$ for $m \neq 0$ and $a(0) = - \frac{1}{2} c(1,-1)$, we find \begin{equation} \begin{split} c(m,0) &\to c(m,0) + m a(m) = 0,~~ \forall~m \neq 0 \\ c(1,-1) &\to c(1,-1) + 2 a(0) = 0 \end{split} \end{equation} We can use this redefinition to set $c(m,0) = c(0,m) = 0$ and $c(1,-1) = 0$. The conformal algebra then takes the form \begin{equation} \begin{split} \left[ L_m, L_0 \right] &= m L_m,~~ \left[ L_1, L_{-1} \right] = 2 L_0 \end{split} \end{equation} while the remaining generators satisfies the same old algebra. Consider now the following Jacobi Identity for $m,n\neq 0$ and $m+n\neq0$. \begin{equation} \begin{split} 0 &= \left[ \left[ L_m, L_n \right], L_0 \right] + \left[ \left[ L_n, L_0 \right], L_m \right] + \left[ \left[ L_0, L_m \right], L_n \right] = - \left( m + n \right) c (m,n) \\ \end{split} \end{equation} Since $m+n\neq0$, we must have $c(m,n) = 0$. Putting it all together, we find $c(m,n) = a(m) \delta_{m+n,0}$. We then find that the most general central extension of the Witt algebra takes the form \begin{equation} \begin{split} \left[ L_m, L_n \right] = (m-n) L_{m+n} + a(m) \delta_{m+n,0} \end{split} \end{equation} where $a(\pm 1) = 0$ (from $c(1,-1) = 0$) and $a(m) = a(-m)$. The functional form of $a(m)$ can be set by looking at a generic Jacobi Identity \begin{equation} \begin{split} 0 &= \left[ \left[ L_m, L_n \right], L_p \right] + \left[ \left[ L_p, L_m \right], L_n \right] + \left[ \left[ L_n, L_p \right], L_m \right] \\ &= (m-n)\left[ L_{m+n} , L_p \right] + (p-m) \left[ L_{p+m} , L_n \right] + (n-p)\left[ L_{n+p}, L_m \right] \\ &= \left[ (m-n)a(m+n) - ( 2m + n ) a(n) + (m+2n)a(m) \right] \delta_{n+p+m,0} \\ \end{split} \end{equation} We then get \begin{equation} \begin{split} (m-n)a(m+n) - ( 2m + n ) a(n) + (m+2n)a(m) \end{split} \end{equation} For $m=1$, we get \begin{equation} \begin{split} (m-1)a(m+1) - (m+2)a(m) = 0 \implies \frac{a(m+1)}{a(m)} = \frac{m+2}{m-1} \end{split} \end{equation} We then have \begin{equation} \begin{split} a(m) &= \frac{a(m)}{a(m-1)} \frac{a(m-1)}{a(m-2)} \cdots \frac{a(3)}{a(2)} \\ &= \frac{m+1}{m-2} \frac{m}{m-3} \frac{m-1}{m - 4} \frac{m-2}{m-5} \cdots \frac{4}{3} \\ &= \frac{a(2)}{6} m(m^2-1) \end{split} \end{equation} We define $a(2) = \frac{c}{2}$. The most general central extension of the Witt algebra then takes the form \begin{equation} \begin{split} \boxed{ \left[ L_m, L_n \right] = \left( m - n \right) L_{m+n} + \frac{c}{12} m \left( m^2 - 1 \right) \delta_{m+n,0} } \end{split} \end{equation} This algebra is called the Virasoro algebra and is denoted by ${\cal L}_c$. It is parameterized by a single number $c$, called the central charge of the theory.

  • $\begingroup$ Your derivation is somewhat different than from the book, but I think I know what I missed. You said it's obvious that $c(m,n)=-c(n,m)$, and that wasn't clear to me, but then I remembered that Lie bracket anticommute ($[L_m,L_n]=-[L_n,L_m]$), and then the obviousness is apparent :D Thank you :) That was the part that was missing for all the rest. When I went through the derivation in the book I could follow it, but this was the piece that was missing :D $\endgroup$
    – dingo_d
    Oct 13 '13 at 20:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.